Fool's gold why the Internet is no substitute for a library - Herring, Mark Y. 1952- (McFarland, 2007)
"This work skeptically explores the notion that the Internet will soon obviate any need for traditional print-based academic libraries, and makes a case for the library's staying power in the face of technological advancements"--Provided by publisher